2012
DOI: 10.1063/1.4707336
|View full text |Cite
|
Sign up to set email alerts
|

Structural and spectroscopic study of the van der Waals complex of CO with HCO+ and the isoelectronic complex of CS with HCS+

Abstract: This work reports the results of high level ab initio calculations of the OC-HCO(+) complex and the SC-HCS(+) complex and their hydrogen migration transition states. Geometry optimizations are performed at the CCSD(T)/aug-cc-pV5Z level of theory. Subsequent frequency calculations are carried out at the CCSD(T)/aug-cc-pVQZ level of theory. Additional geometry optimizations and harmonic frequency calculations for all the species involved in this study have been done with the explicitly correlated CCSD(T)-F12 met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 65 publications
(65 reference statements)
2
10
0
Order By: Relevance
“…Hence, the C ∞v VPT2 vibrationally averaged (R α ) geometry, as provided in Table V of the supplementary material, 26 may not be what experiments may interpret as the observed geometry. The equilibrium values are similar and corroborate previous CCSD(T)/aug-cc-pV5Z results, 13 as well as the proposition by Klemperer and Vaida 11 that OCHCO + can be thought of as "a gas-phase" zwitterion where the interconversion between the two minima propagates a continuous hydrogen bond/covalent bond exchange. However, the low proton-motion barrier complicates such classifications especially when examining the vibrational frequencies of OCHCO + .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Hence, the C ∞v VPT2 vibrationally averaged (R α ) geometry, as provided in Table V of the supplementary material, 26 may not be what experiments may interpret as the observed geometry. The equilibrium values are similar and corroborate previous CCSD(T)/aug-cc-pV5Z results, 13 as well as the proposition by Klemperer and Vaida 11 that OCHCO + can be thought of as "a gas-phase" zwitterion where the interconversion between the two minima propagates a continuous hydrogen bond/covalent bond exchange. However, the low proton-motion barrier complicates such classifications especially when examining the vibrational frequencies of OCHCO + .…”
Section: Resultssupporting
confidence: 78%
“…The CcCR harmonic frequencies at the minimum are given in the supplementary material 26 and are in good agreement with the CCSD(T)/aug-cc-pVQZ values provided earlier 13 as well as the CCSD(T)-F12/cc-pVTZ-F12 values also computed in the same study. The harmonic frequencies from the PES, given in the supplementary material, 26 agree well with the benchmark CcCR ones, although some differences as large as 20 cm −1 are seen.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…As a result, such vibrational transitions are incredibly strong absorbers/emitters meaning that small column densities of materials are required to create observable spectral features. OCHCO + , NNHNN + , and the heteromolecular combinations have been analyzed recently showing that these bright vibrational modes can be found from the near-to mid-and even far-IR wavelengths (Terrill & Nesbitt 2010;Cotton et al 2012;Yu et al 2015;Fortenberry, Lee & Francisco 2016b,a;Begum & Subramanian 2016) making them tantalizing targets for the epoch for growth in IR telescopic power in which we are currently in the midst.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the nature of the known and potential C—S triply bonded molecules has been analyzed at various state‐of‐art theory levels by Denis and Iribarne and Rzepa . The structure and spectroscopic study of the isoelectronic complex of CS with HCS + was reported by Cotton et al In contrast, the history of the SBe bond is quite short. The triatomic molecules SBeNg (where Ng is a noble gas) were studied by Borocci et al The bonding nature of SBe was not discussed, though it could be expected to be of triple bonding as BeO in BeONg .…”
Section: Introductionmentioning
confidence: 99%